The Relative Reinforcing Value of Cookies Is Higher Among Head Start Preschoolers With Obesity - Eagleton, Sally G.; Temple, Jennifer L.; Keller, Kathleen L.; Marini, Michele E.; Savage, Jennifer S. (Frontiers in Psychology, 2021)
*With the addition of statistical analysis and results as requested by reviewers, I was unable to meet the required word limit.